2018
DOI: 10.1016/j.ejmech.2018.07.006
|View full text |Cite
|
Sign up to set email alerts
|

Crystal structure of the Eg5 - K858 complex and implications for structure-based design of thiadiazole-containing inhibitors

Abstract: The thiadiazole scaffold is an important core moiety in a variety of clinical drug candidates targeting a range of diseases. For example, the 2,4,5-substituted 1,3,4-thiadiazole scaffold is present in a lead compound and at least two clinical candidates targeting the human motor protein Eg5, against neoplastic diseases. An inhibitor named K858 has in vivo activity in various mouse xenografts whereas the clinical candidates (S)-ARRY-520 and (R)-Litronesib have entered clinical trials with the former one in phas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 47 publications
1
16
0
Order By: Relevance
“…As reported in the literature, Eg5 inhibition results in the formation of monoaster spindles which is thought to lead to mitotic catastrophe and apoptosis [22]. This aspect, which is dose-dependent, is clearly demonstrated in our experimental model where compounds 2 , 41 and K858 , by inhibiting Eg5 protein, lead to the formation of several monopolar spindles [12]. Mitotic braking, due to an improper mitotic spindle formation, may result in the induction of apoptosis by activating several pro-apoptotic factors, among which Bax and Caspases are included [23].…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…As reported in the literature, Eg5 inhibition results in the formation of monoaster spindles which is thought to lead to mitotic catastrophe and apoptosis [22]. This aspect, which is dose-dependent, is clearly demonstrated in our experimental model where compounds 2 , 41 and K858 , by inhibiting Eg5 protein, lead to the formation of several monopolar spindles [12]. Mitotic braking, due to an improper mitotic spindle formation, may result in the induction of apoptosis by activating several pro-apoptotic factors, among which Bax and Caspases are included [23].…”
Section: Discussionsupporting
confidence: 77%
“…Potent kinesin Eg5 inhibitors, compounds 2 , 4 , 26 , 30 , 31 , 41 , and 44 , characterized by the thiadiazoline nucleus present in the structure of K858 and endowed with different substituents at C5 (Figure 1), were enrolled in this study on the basis of the reported in vitro inhibition of the basal Eg5 ATPase activity in the range 0.84 < IC 50 (μM) < 7.5 [12].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Both compounds contain a main 1,3,4-thiadiazole ring with a 5-phenyl group ( fig. S5A and B), which is important for binding to the hydrophobic pocket of the KSP allosteric site (34). Both compounds have nanomolar IC50 values for KSP enzymatic activity in vitro and subnanomolar IC50 values for reducing viability of cells in culture (21,22), and each exhibits a maximum tolerated dose in mg/kg in mice (20,23), fig.…”
Section: Inhibition Of Neuroblastoma Cell Viability By Arry-520 and Amentioning
confidence: 99%
“…47 Evidence is available in the literature, supporting the fact that different inhibitors target Eg5 differently, 48 in normal, aberrant, and degenerative manner; furthermore, novel drug development strategies are under clinical trials. 49,50 Chen et al 41 contrasting effects of a group of inhibitors on Eg5 motor proteins.…”
Section: Resultsmentioning
confidence: 99%